Global availability of guidelines related to assistive technology: a scoping review - Zhang, Wei; Borg, Johan (Frontiers in Rehabilitation Sciences, 2025)
BackgroundGiven the rising global demand for assistive technology, predicted to encompass 3.5 billion people by 2050, understanding the availability of guidelines governing its use and identifying potential gaps is paramount.ObjectiveThis scoping review mapped existing guidelines related to assistive technology. The review aimed to inform future research and guideline development to accelerate access to assistive technology within universal health coverage.MethodsFollowing the JBI methodology, a systematic search of guidelines published between January 2008 and March 2024 was conducted across CINAHL, Google Scholar, PubMed, TRIP and WHO IRIS. Included guidelines related to specific assistive technology, including product types and services for users and their caregivers. Guidelines targeting system-level interventions were excluded.ResultsThe search identified 291 records, of which 24 guidelines were included. They focus on improving health outcomes for diverse populations across different healthcare settings. Most guidelines originated from high-income countries and predominantly addressed commonly known assistive products for mobility, hearing, vision, and self-care. There is a gap in guidelines for assistive products for cognition and communication. The identified guidelines primarily followed evidence-based methodologies and involved assistive technology users in their development.ConclusionsThis review provides a crucial overview of the existing landscape of assistive technology guidelines. It calls for further action to harmonize standards, leverage innovation in evidence generation, and enhance guideline development to better serve the global population in need of assistive technology.